Solid waste based geopolymer and preparation method and application thereof

By stirring and mixing coal gasification slag, slag, alkali slag, phosphogypsum and sand and adding water, the solid waste base polymer is prepared, and the strong alkaline excitation of alkali slag and phosphogypsum is used to generate hydration products, solving the problem of ineffective utilization of solid waste, and realizing the preparation of high-strength polymers and the comprehensive utilization of solid waste.

CN119707333APending Publication Date: 2025-03-28CHINA ENERGY GRP NINGXIA COAL IND CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411729407.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, solid waste such as coal gasification slag and phosphogypsum cannot be effectively utilized, resulting in waste of land resources and increasing ecological environment pressure.

Method used

By stirring and mixing coal gasification slag, slag, alkali slag, phosphogypsum and sand, and adding appropriate amount of water, a solid waste base polymer is prepared. The strong alkaline excitation and excitation slag and coal gasification slag matrix of alkali slag and phosphogypsum are used to generate hydration products with gelling properties.

Benefits of technology

The efficient and comprehensive utilization of solid waste is achieved, and the preparation of geopolymers with high mechanical strength can greatly replace traditional silicate cement, reduce production costs, and promote sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005159895440000091
    Figure BDA0005159895440000091
Patent Text Reader

Abstract

The invention provides a solid waste-based geopolymer and a preparation method and application thereof, the solid waste-based geopolymer comprises the following components: coal gasification slag, slag, alkaline residue, ardealite and sand, and the weight ratio of the coal gasification slag to the slag to the alkaline residue to the ardealite is (30-45): (30-45): (5-20): (5-20); the weight ratio of the sand to the sum of the weight of the coal gasification slag, the slag, the alkaline residues and the ardealite is (3-5): 1. The solid waste-based geopolymer disclosed by the invention has high strength, realizes effective comprehensive utilization of various solid wastes, and solves the problem that solid wastes such as coal gasification slag and phosphogypsum cannot be effectively utilized in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of building materials, and in particular to a solid waste-based polymer and a preparation method and application thereof. Background Art

[0002] Coal gasification slag is a byproduct of converting the effective components in coal into crude synthesis gas such as gasoline, diesel, ethers and alcohols. According to statistics, my country's coal gasification slag emissions exceed 60 million tons per year, and it is currently mainly treated by storage and landfill, with an utilization rate of less than 50%. Phosphogypsum is a large solid waste discharged during the production of wet phosphoric acid. At present, the accumulation of phosphogypsum in my country has exceeded 400 million tons, and it is increasing at a rate of 80 million tons per year. On average, about 4.5 to 5 tons of phosphogypsum are produced for every ton of phosphoric acid produced. Coal gasification slag and phosphogypsum are continuously piled up over a large area, and there is currently no effective means of large-scale utilization. This not only seriously wastes land resources, but also puts great pressure on the ecological environment. Therefore, how to effectively use the above-mentioned solid waste to prepare geopolymers with high mechanical strength is of great significance. Summary of the invention

[0003] The main purpose of the present invention is to provide a solid waste-based polymer and a preparation method and application thereof, so as to solve the problem in the prior art that solid wastes such as coal gasification slag and phosphogypsum cannot be effectively utilized.

[0004] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a solid waste-based polymer is provided, comprising the following components: coal gasification slag, slag, alkali slag, phosphogypsum and sand, the weight ratio of the coal gasification slag, slag, alkali slag and phosphogypsum is (30-45): (30-45): (5-20): (5-20); the weight ratio of sand to the sum of the weight of coal gasification slag, slag, alkali slag and phosphogypsum is (3-5): 1.

[0005] Furthermore, the weight ratio of coal gasification slag, slag, alkaline slag and phosphogypsum is (30-32): (30-32): (15-17): (15-17).

[0006] Furthermore, the particle size of the coal gasification slag is less than 0.03 mm.

[0007] Furthermore, the slag is S95 grade ore powder.

[0008] Furthermore, the particle size of the alkali residue is less than 200 meshes.

[0009] Furthermore, the particle size of the phosphogypsum is less than 200 mesh.

[0010] Furthermore, the sand is gangue sand, with a particle size of less than or equal to 2.36 mm and a mud content of <3%.

[0011] Furthermore, the coal gasification slag is obtained by ball milling the coal gasification slag waste.

[0012] Furthermore, phosphogypsum is obtained by sequentially drying, grinding and sieving phosphogypsum waste.

[0013] Furthermore, the alkali residue is prepared by the following steps: the alkali residue stock solution is allowed to stand for 5 to 7 days for stratification, and the precipitated layer is dried, ground, and sieved through a sieve in sequence to obtain the alkali residue.

[0014] Furthermore, the initial water content of the alkali residue stock solution is not less than 90%.

[0015] Furthermore, in terms of weight percentage, the CaO content in the alkali slag is greater than 40%.

[0016] According to another aspect of the present invention, a method for preparing a solid waste-based polymer is provided, comprising the following steps:

[0017] Step S1, mixing coal gasification slag, slag, alkaline slag, phosphogypsum and sand to obtain a mixture;

[0018] Step S2, adding water to the mixture and stirring to obtain a solid waste-based polymer;

[0019] Among them, the weight ratio of coal gasification slag, slag, alkali slag and phosphogypsum is (30-45): (30-45): (5-20): (5-20); the weight ratio of sand to the sum of the weight of coal gasification slag, slag, alkali slag and phosphogypsum is (3-5): 1; the weight ratio of added water to solid waste base polymer is (0.12-0.15): 1.

[0020] According to another aspect of the present invention, there is provided use of the above solid waste-based polymer or the solid waste-based polymer prepared according to the above preparation method in road construction.

[0021] According to another aspect of the present invention, there is provided a roadbed material as above, comprising a hardened product of the solid waste-based polymer as above or the solid waste-based polymer prepared according to the preparation method as above;

[0022] Preferably, the solid waste-based polymer is loaded into a mold coated with a release agent and the mold is placed on a vibration table, the solid waste-based polymer is vibrated into shape, the molded solid waste-based polymer is cured for 20 to 30 hours and then demolded, and after demolding, it is cured for 7 to 28 days at a temperature of 18° C. to 22° C. and a relative humidity of 93% to 97% to obtain a hardened product.

[0023] By applying the technical solution of the present invention, the solid waste base polymer uses solid waste coal gasification slag, slag, alkali slag, and phosphogypsum as raw materials, and uses the strong alkalinity of alkali slag and phosphogypsum to stimulate the slag and coal gasification slag matrix to generate hydration products with gelling properties. In addition, the aragonite and other cementing materials in the alkali slag can participate in the formation of geopolymers during the excitation process, which helps to increase the strength of its internal structure. The incorporation of phosphogypsum can increase the content of chemically bound water in the geopolymer, which helps to form more hydration products, thereby improving the strength of the geopolymer, and the CaSO4 in the phosphogypsum can react with the aluminum in the raw material to generate hydration products such as calcium sulfonate, which will fill the pores inside the geopolymer and increase its density, thereby obtaining a high-strength geopolymer, and at the same time realize the effective comprehensive utilization of multiple solid wastes and reduce solid waste emissions. Furthermore, compared with the traditional geopolymer using alkaline activators such as NaOH or water glass, the use of alkali slag and phosphogypsum as alkaline activators significantly reduces the consumption of chemical raw materials and can reduce production costs.

[0024] The solid waste-based polymer of the present invention has high strength and realizes comprehensive utilization of solid waste, can largely replace traditional silicate cement, is beneficial to environmental protection, reduces production costs and promotes the realization of sustainable development goals, and has broad application prospects. DETAILED DESCRIPTION

[0025] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0026] As described in the background art, there is a problem in the prior art that a large amount of coal gasification slag and phosphogypsum are continuously piled up over a large area and cannot be effectively and scaled up. In order to solve the above problem, according to one aspect of the present invention, a solid waste base polymer is provided, comprising the following components: coal gasification slag, slag, alkali slag, phosphogypsum and sand, the weight ratio of coal gasification slag, slag, alkali slag and phosphogypsum is (30-45): (30-45): (5-20): (5-20); the weight ratio of sand to the sum of the weight of coal gasification slag, slag, alkali slag and phosphogypsum is (3-5): 1.

[0027] Coal gasification slag is a solid waste produced in the gasification process of coal-to-oil, and has a certain volcanic ash activity. Slag is an industrial waste residue produced in the process of steel production, mainly containing minerals such as silicates, aluminates and calcium oxide, which can provide a stable source of silicate aluminates for the geopolymerization process. Alkali slag is a waste residue produced in the process of industrial ammonia production of Na2CO3. Its annual output is large, and it is mostly piled in the open air. However, the high soluble chloride salts have caused a serious burden on the soil environment. Phosphogypsum is a large amount of solid waste discharged in the production process of wet phosphoric acid. Based on the solid waste base polymer of the present invention, the solid waste base polymer uses solid waste coal gasification slag, slag, alkali slag, and phosphogypsum as raw materials, and uses the strong alkalinity of alkali slag and phosphogypsum to excite the slag and coal gasification slag matrix to generate hydration products with gelling properties. In addition, aragonite and other cementing materials in the alkali slag can participate in the formation of geopolymers during the excitation process, which helps to increase the strength of its internal structure. The addition of phosphogypsum can increase the content of chemically bound water in geopolymers, which helps to form more hydration products, thereby improving the strength of geopolymers. The CaSO4 in phosphogypsum can react with the aluminum in the raw materials to generate hydration products such as calcium sulfonate. These hydration products will fill the pores inside the geopolymer and increase its density, thereby obtaining high-strength geopolymers. At the same time, it realizes the effective comprehensive utilization of multiple solid wastes and reduces solid waste emissions. In addition, alkali slag mainly generates gel-like products such as hydrated calcium silicate and hydrated calcium aluminate through alkaline excitation and hydration reaction, focusing on improving the overall strength and overall density of the material. Phosphogypsum mainly generates calcium sulfonate and hydrated calcium silicate, focusing on shortening the hydration induction period and improving the pore structure, improving the early compressive strength and durability. The two can significantly improve the strength of geopolymers in synergy. Finally, compared with the traditional geopolymers using alkaline activators such as NaOH or water glass, the use of alkali slag and phosphogypsum as alkaline activators significantly reduces the consumption of chemical raw materials and can reduce production costs. The solid waste-based polymer of the present invention has high strength and realizes comprehensive utilization of solid waste, can largely replace traditional silicate cement, is beneficial to environmental protection, reduces production costs and promotes the realization of sustainable development goals, and has broad application prospects.

[0028] In some embodiments, the weight ratio of coal gasification slag, slag, alkaline slag and phosphogypsum is (30-32): (30-32): (15-17): (15-17), so as to obtain a higher strength and durability solid waste-based polymer, more effectively convert various wastes into high-quality building materials, and realize the resource recycling of solid waste.

[0029] In some embodiments, the particle size of the coal gasification slag is less than 0.03 mm. Controlling the coal gasification slag is beneficial to improving the uniformity of the coal gasification slag, obtaining higher strength solid waste-based polymer products, and improving product production efficiency.

[0030] In some embodiments, in order to obtain a higher strength solid waste-based polymer product, the slag is S95 grade mineral powder.

[0031] In some embodiments, in order to obtain a higher strength solid waste-based polymer product, the particle size of the alkali residue is less than 200 mesh.

[0032] In some embodiments, in order to obtain higher strength solid waste-based polymer products, the particle size of the phosphogypsum is less than 200 mesh.

[0033] In some embodiments, in order to obtain a higher strength solid waste-based polymer product, the sand is gangue sand with a particle size of less than or equal to 2.36 mm and a mud content of <3%.

[0034] In some embodiments, the coal gasification slag is obtained by ball milling coal gasification slag waste, which has high production efficiency and is suitable for large-scale production.

[0035] In some embodiments, phosphogypsum is obtained by sequentially drying, grinding, and sieving phosphogypsum waste, which is conducive to obtaining powdered phosphogypsum with good dispersibility and uniform particle size.

[0036] In some embodiments, the alkali residue is prepared by the following steps: the alkali residue stock solution is allowed to stand for 5 to 7 days for stratification, and the precipitated layer is dried, ground, and sieved through a sieve in sequence to obtain the alkali residue. The alkali residue stock solution is treated by the above process to obtain the alkali residue, and the process is simple and the alkali residue recovery rate is high.

[0037] In some embodiments, the initial water content of the alkali residue raw solution is not less than 90%.

[0038] In some embodiments, the CaO content in the alkali residue is greater than 40% by weight. The high content of calcium oxide in the alkali residue makes the alkali residue highly alkaline, and its synergistic effect with other components in the alkali residue (such as Na2O) can stimulate the activity of coal gasification slag and slag, promote hydration reaction, and improve the mechanical properties of the material. The high content of calcium oxide in the alkali residue can react with the active ingredients in the coal gasification slag and water to generate hydraulic gel-like substances such as hydrated calcium silicate (CSH) and calcium sulfonate (AFt) to improve the mechanical strength of the material, and by generating hydration products such as calcium sulfonate, the microstructure of the slag can be improved, making the material denser, thereby improving its compressive strength, thereby improving the strength and stability of the solid waste-based polymer. A high content of calcium oxide can accelerate the hydration reaction of phosphogypsum, promote the formation of hydration products such as ettringite and hydrated calcium silicate, improve the strength and durability of phosphogypsum, and by generating hydration products such as ettringite, it can improve the pore structure of phosphogypsum, reduce porosity, and increase the density and compressive strength of the material, thereby obtaining a solid waste-based polymer with high mechanical strength.

[0039] According to another aspect of the present invention, a method for preparing a solid waste-based polymer is provided, comprising the following steps:

[0040] Step S1, mixing coal gasification slag, slag, alkaline slag, phosphogypsum and sand to obtain a mixture;

[0041] Step S2, adding water to the mixture and stirring to obtain a solid waste-based polymer;

[0042] Among them, the weight ratio of coal gasification slag, slag, alkali slag and phosphogypsum is (30-45): (30-45): (5-20): (5-20); the weight ratio of sand to the sum of the weight of coal gasification slag, slag, alkali slag and phosphogypsum is (3-5): 1; the weight ratio of added water to solid waste base polymer is (0.12-0.15): 1.

[0043] According to another aspect of the present invention, there is provided use of the above solid waste-based polymer or the solid waste-based polymer prepared according to the above preparation method in road construction.

[0044] According to another aspect of the present invention, there is provided a roadbed material as described above, comprising a hardened product of the solid waste-based polymer as described above or the solid waste-based polymer prepared according to the preparation method as described above.

[0045] Preferably, the solid waste-based polymer is loaded into a mold coated with a release agent and the mold is placed on a vibration table, the solid waste-based polymer is vibrated into shape, the molded solid waste-based polymer is cured for 20 to 30 hours and then demolded, and after demolding, it is cured for 7 to 28 days at a temperature of 18° C. to 22° C. and a relative humidity of 93% to 97% to obtain a hardened product.

[0046] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0047] Unless otherwise specified, the raw materials and reagents used in the examples and comparative examples were commercially available.

[0048] Example 1

[0049] A solid waste-based polymer comprises the following components: coal gasification slag, slag, alkaline slag (calculated by weight percentage, the CaO content in the alkaline slag is 44.79%), phosphogypsum and sand, wherein the weight ratio of the coal gasification slag, slag, alkaline slag and phosphogypsum is 40:40:10:10; the weight ratio of sand to the sum of the weight of the coal gasification slag, slag, alkaline slag and phosphogypsum is 4:1;

[0050] The coal gasification slag is obtained by ball milling the coal gasification slag waste for 80 minutes, and the particle size is less than 0.03 mm;

[0051] The slag is S95 grade ore powder;

[0052] The sand is gangue sand, with a particle size of less than or equal to 2.36 mm and a mud content of less than 3%;

[0053] The phosphogypsum is obtained by drying, grinding and sieving the phosphogypsum waste in sequence;

[0054] The alkali residue is prepared by the following steps: the alkali residue stock solution is allowed to stand for 6 days for stratification, and the precipitated layer is dried, ground, and sieved through a 200-mesh sieve to obtain the alkali residue.

[0055] The steps for preparing solid waste-based polymers are as follows:

[0056] Step 1: add 0.20 kg of coal gasification slag, 0.20 kg of slag, 0.05 kg of alkali residue, 0.05 kg of phosphogypsum, and 2.0 kg of sand into a forced mixer in sequence and mix well to obtain a mixture;

[0057] Step 2: Add 0.3736 kg of mixed water to the mixture and stir evenly to obtain a solid waste-based polymer.

[0058] Example 2

[0059] A solid waste-based polymer comprises the following components: coal gasification slag, slag, alkaline slag (calculated by weight percentage, the CaO content in the alkaline slag is 44.79%), phosphogypsum and sand, wherein the weight ratio of the coal gasification slag, slag, alkaline slag and phosphogypsum is 30:30:15:15; the weight ratio of sand to the sum of the weight of the coal gasification slag, slag, alkaline slag and phosphogypsum is 4:1;

[0060] The coal gasification slag is obtained by ball milling the coal gasification slag waste for 80 minutes, and the particle size is less than 0.03 mm;

[0061] The slag is S95 grade ore powder;

[0062] The sand is gangue sand, with a particle size of less than or equal to 2.36 mm and a mud content of less than 3%;

[0063] The phosphogypsum is obtained by drying, grinding and sieving the phosphogypsum waste in sequence;

[0064] The alkali residue is prepared by the following steps: the alkali residue stock solution is allowed to stand for 6 days for stratification, and the precipitated layer is dried, ground, and sieved through a 200-mesh sieve to obtain the alkali residue.

[0065] The steps for preparing solid waste-based polymers are as follows:

[0066] Step 1: add 0.175 kg of coal gasification slag, 0.175 kg of slag, 0.075 kg of alkali residue, 0.075 kg of phosphogypsum and 2.0 kg of phosphogypsum into a forced mixer in sequence and mix well to obtain a mixture;

[0067] Step 2: Add 0.3736 kg of mixed water to the mixture and stir evenly to obtain a solid waste-based polymer.

[0068] Example 3

[0069] A solid waste-based polymer comprises the following components: coal gasification slag, slag, alkaline slag (calculated by weight percentage, the CaO content in the alkaline slag is 44.79%), phosphogypsum and sand, wherein the weight ratio of the coal gasification slag, slag, alkaline slag and phosphogypsum is 30:30:20:20; the weight ratio of sand to the sum of the weight of the coal gasification slag, slag, alkaline slag and phosphogypsum is 4:1;

[0070] The coal gasification slag is obtained by ball milling the coal gasification slag waste for 80 minutes, and the particle size is less than 0.03 mm;

[0071] The slag is S95 grade ore powder;

[0072] The sand is gangue sand, with a particle size of less than or equal to 2.36 mm and a mud content of less than 3%;

[0073] The phosphogypsum is obtained by drying, grinding and sieving the phosphogypsum waste in sequence;

[0074] The alkali residue is prepared by the following steps: the alkali residue stock solution is allowed to stand for 6 days for stratification, and the precipitated layer is dried, ground, and sieved through a 200-mesh sieve to obtain the alkali residue.

[0075] The steps for preparing solid waste-based polymers are as follows:

[0076] Step 1: add 0.15 kg of coal gasification slag, 0.15 kg of slag, 0.10 kg of alkali residue, 0.10 kg of phosphogypsum, and 2.0 kg of phosphogypsum into a forced mixer in sequence and mix well to obtain a mixture;

[0077] Step 2: Add 0.3736 kg of mixed water to the mixture and stir evenly to obtain a solid waste-based polymer.

[0078] Example 4

[0079] The only difference from Example 1 is that the weight ratio of sand to the sum of the weight of coal gasification slag, slag, alkaline slag and phosphogypsum is 3:1. The specific steps are as follows:

[0080] A solid waste-based polymer comprises the following components: coal gasification slag, slag, alkaline slag, phosphogypsum and sand, wherein the weight ratio of the coal gasification slag, slag, alkaline slag and phosphogypsum is 40:40:10:10; the weight ratio of sand to the sum of the weight of the coal gasification slag, slag, alkaline slag and phosphogypsum is 3:1;

[0081] The coal gasification slag is obtained by ball milling the coal gasification slag waste for 80 minutes, and the particle size is less than 0.03 mm;

[0082] The slag is S95 grade ore powder;

[0083] The sand is gangue sand, with a particle size of less than or equal to 2.36 mm and a mud content of less than 3%;

[0084] The phosphogypsum is obtained by drying, grinding and sieving the phosphogypsum waste in sequence;

[0085] The alkali residue is prepared by the following steps: the alkali residue stock solution is allowed to stand for 6 days for stratification, and the precipitated layer is dried, ground, and sieved through a 200-mesh sieve to obtain the alkali residue.

[0086] The steps for preparing solid waste-based polymers are as follows:

[0087] Step 1: add 0.25 kg of coal gasification slag, 0.25 kg of slag, 0.0625 kg of alkali residue, 0.0625 kg of phosphogypsum, and 1.875 kg of sand into a forced mixer in sequence and mix well to obtain a mixture;

[0088] Step 2: Add 0.3736 kg of mixed water to the mixture and stir evenly to obtain a solid waste-based polymer.

[0089] Example 5

[0090] The only difference from Example 1 is that the weight ratio of sand to the sum of the weight of coal gasification slag, slag, alkali slag and phosphogypsum is 5:1, as follows:

[0091] A solid waste-based polymer comprises the following components: coal gasification slag, slag, alkaline slag, phosphogypsum and sand, wherein the weight ratio of the coal gasification slag, slag, alkaline slag and phosphogypsum is 40:40:10:10; and the weight ratio of sand to the sum of the weight of the coal gasification slag, slag, alkaline slag and phosphogypsum is 5:1;

[0092] The coal gasification slag is obtained by ball milling the coal gasification slag waste for 80 minutes, and the particle size is less than 0.03 mm;

[0093] The slag is S95 grade ore powder;

[0094] The sand is gangue sand, with a particle size of less than or equal to 2.36 mm and a mud content of less than 3%;

[0095] The phosphogypsum is obtained by drying, grinding and sieving the phosphogypsum waste in sequence;

[0096] The alkali residue is prepared by the following steps: the alkali residue stock solution is allowed to stand for 6 days for stratification, and the precipitated layer is dried, ground, and sieved through a 200-mesh sieve to obtain the alkali residue.

[0097] The steps for preparing solid waste-based polymers are as follows:

[0098] Step 1: add 0.1667 kg of coal gasification slag, 0.1667 kg of slag, 0.04167 kg of alkali residue, 0.04167 kg of phosphogypsum, and 2.0833 kg of sand into a forced mixer in sequence and mix well to obtain a mixture;

[0099] Step 2: Add 0.3736 kg of mixed water to the mixture and stir evenly to obtain a solid waste-based polymer.

[0100] Comparative Example 1

[0101] The only difference from Example 1 is that the weight ratio of sand to the sum of the weight of coal gasification slag, slag, alkali slag and phosphogypsum is 6:1, as follows:

[0102] A solid waste-based polymer comprises the following components: coal gasification slag, slag, alkaline slag, phosphogypsum and sand, wherein the weight ratio of the coal gasification slag, slag, alkaline slag and phosphogypsum is 40:40:10:10; and the weight ratio of sand to the sum of the weight of the coal gasification slag, slag, alkaline slag and phosphogypsum is 6:1;

[0103] The coal gasification slag is obtained by ball milling the coal gasification slag waste for 80 minutes, and the particle size is less than 0.03 mm;

[0104] The slag is S95 grade ore powder;

[0105] The sand is gangue sand, with a particle size of less than or equal to 2.36 mm and a mud content of less than 3%;

[0106] The phosphogypsum is obtained by drying, grinding and sieving the phosphogypsum waste in sequence;

[0107] The alkali residue is prepared by the following steps: the alkali residue stock solution is allowed to stand for 6 days for stratification, and the precipitated layer is dried, ground, and sieved through a 200-mesh sieve to obtain the alkali residue.

[0108] The steps for preparing solid waste-based polymers are as follows:

[0109] Step 1: add 0.1429 kg of coal gasification slag, 0.1429 kg of slag, 0.03571 kg of alkali slag, 0.03571 kg of phosphogypsum, and 2.142 kg of sand into a forced mixer in sequence and mix well to obtain a mixture;

[0110] Step 2: Add 0.3736 kg of mixed water to the mixture and stir evenly to obtain a solid waste-based polymer.

[0111] Comparative Example 2

[0112] The only difference from Example 1 is that the phosphogypsum is replaced with alkali slag of equal mass, as follows:

[0113] A solid waste-based polymer comprises the following components: coal gasification slag, slag, alkali slag and sand, wherein the weight ratio of the coal gasification slag, slag and alkali slag is 40:40:20; the weight ratio of sand to the sum of the weight of the coal gasification slag, slag and alkali slag is 4:1;

[0114] The coal gasification slag is obtained by ball milling the coal gasification slag waste for 80 minutes, and the particle size is less than 0.03 mm;

[0115] The slag is S95 grade ore powder;

[0116] The sand is gangue sand, with a particle size of less than or equal to 2.36 mm and a mud content of less than 3%;

[0117] The alkali residue is prepared by the following steps: the alkali residue stock solution is allowed to stand for 6 days for stratification, and the precipitated layer is dried, ground, and sieved through a 200-mesh sieve to obtain the alkali residue.

[0118] The steps for preparing solid waste-based polymers are as follows:

[0119] Step 1: add 0.20 kg of coal gasification slag, 0.20 kg of slag, 0.1 kg of alkali residue and 2.0 kg of sand into a forced mixer in sequence and mix them evenly to obtain a first mixture;

[0120] Step 2: Add 0.3736 kg of mixed water to the mixture and stir evenly to obtain a solid waste-based polymer.

[0121] Comparative Example 3

[0122] The difference between the above method and the embodiment is that the alkali residue is replaced with phosphogypsum of equal mass, as follows:

[0123] A solid waste-based polymer comprises the following components: coal gasification slag, slag, phosphogypsum and sand, wherein the weight ratio of the coal gasification slag, slag and phosphogypsum is 40:40:20; and the weight ratio of the sand to the sum of the weight of the coal gasification slag, slag and phosphogypsum is 4:1;

[0124] The coal gasification slag is obtained by ball milling the coal gasification slag waste for 80 minutes, and the particle size is less than 0.03 mm;

[0125] The slag is S95 grade ore powder;

[0126] The sand is gangue sand, with a particle size of less than or equal to 2.36 mm and a mud content of less than 3%;

[0127] The phosphogypsum is obtained by drying, grinding and sieving the phosphogypsum waste in sequence;

[0128] The steps for preparing solid waste-based polymers are as follows:

[0129] Step 1: 0.20 kg of coal gasification slag, 0.20 kg of slag, 0.1 kg of phosphogypsum and 2.0 kg of sand are sequentially added into a forced mixer and stirred evenly to obtain a first mixture;

[0130] Step 2: Add 0.3736 kg of mixed water to the mixture and stir evenly to obtain a solid waste-based polymer.

[0131] The performance tests of the solid waste-based polymers prepared in Examples 1-3 were performed:

[0132] (1) The solid waste-based polymer is placed in a mold coated with a release agent and pounded evenly. After pounding evenly, the mold is placed on a vibration table to vibrate the solid waste-based polymer into shape. The molded solid waste-based polymer is cured for 24 hours and then demolded. After demolding, it is cured for 3 days, 7 days, 14 days, and 28 days at a temperature of 20±0.5°C and a relative humidity of 95±2%, respectively, to obtain a series of hardened products.

[0133] (2) The compressive strength of the hardened products was tested after different curing days. The test results are shown in Table 1.

[0134] Table 1

[0135]

[0136] Compared with Comparative Examples 1-3, the material strength of the hardened products prepared using the solid waste-based polymers in Examples 1-5 is significantly increased.

[0137] It can be seen from Example 1, Example 4, Example 5 and Comparative Example 1 that when the ratio of sand material to cementitious material is reduced from 6:1 to 3:1, the strength of the hardened product material increases. As the cementitious material ratio increases, there is enough cementitious material to combine with the sand material to fill the large pores between the sand materials, thereby improving the strength of the solid waste base polymerization.

[0138] From the comparison of Example 1 and Comparative Example 2, it can be seen that only adding alkali activator alkali slag without adding phosphogypsum will cause the strength of the hardened product prepared by the geopolymer, especially the initial strength, to decrease significantly. In addition to being an alkali activating component, the high content of calcium sulfate in phosphogypsum is conducive to hydration to generate a large amount of hydrated calcium silicate, calcium sulfonate and other gel-like substances. These gel-like substances can fill the pores inside the material, reduce the porosity, improve the density of the material, strengthen the combination between the sand material and the cementitious material, and help to improve the strength of the initial curing product, thereby improving the strength of the solid waste base polymer. From Example 1 and Comparative Example 3, it can be seen that only adding alkali activator phosphogypsum will cause the strength of the hardened product prepared by the geopolymer at each curing stage to decrease. Alkali slag has a high content of calcium oxide, which can react with water to generate calcium hydroxide, thereby promoting the formation of hydration products and improving the strength of the product. In addition, the high content of calcium oxide can also generate gel-like substances such as calcium silicate and calcium sulfonate in the subsequent stage, thereby improving the overall compressive strength of the material and the overall density of the material. It can be seen that the use of alkali slag and phosphogypsum as alkali activators has an important influence on the strength of geopolymers. By adding the two and adjusting the ratio of each raw material, the strength of geopolymers can be effectively improved, and the comprehensive utilization of various solid wastes can be achieved.

[0139] As shown in Table 1, after 7 days of curing, the strength of the hardened product material reached more than 7MPa, which is significantly higher than the minimum strength requirement of 5MPa for road foundation in my country. The product prepared based on the solid waste base polymer of the present invention has high strength and realizes the comprehensive utilization of solid waste, can largely replace traditional silicate cement, is beneficial to environmental protection, reduces production costs and promotes the realization of sustainable development goals, and has broad application prospects.

[0140] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A solid waste-based polymer, characterized in that: The invention comprises the following components: coal gasification slag, slag, alkaline slag, phosphogypsum and sand, wherein the weight ratio of the coal gasification slag, the slag, the alkaline slag and the phosphogypsum is (30-45): (30-45): (5-20): (5-20); the weight ratio of the sand to the sum of the weight of the coal gasification slag, the slag, the alkali slag and the phosphogypsum is (3-5):

1.

2. The solid waste-based polymer according to claim 1, characterized in that: The weight ratio of the coal gasification slag, the slag, the alkaline slag and the phosphogypsum is (30-32): (30-32): (15-17): (15-17).

3. The solid waste-based polymer according to claim 1 or 2, characterized in that: The particle size of the coal gasification slag is less than 0.03 mm; and / or, The slag is S95 grade slag powder; and / or, The particle size of the alkali residue is less than 200 mesh; The particle size of the phosphogypsum is less than 200 mesh; and / or, The sand is gangue sand, with a particle size of less than or equal to 2.36 mm and a mud content of less than 3%.

4. The solid waste-based polymer according to claim 1 or 2, characterized in that: The coal gasification slag is obtained by ball milling coal gasification slag waste; and / or The phosphogypsum is obtained by sequentially drying, grinding and screening phosphogypsum waste.

5. The solid waste-based polymer according to claim 1 or 2, characterized in that: The alkali residue is prepared by the following steps: The alkali residue stock solution is allowed to stand for 5 to 7 days to be layered, and the precipitated layer is dried, ground, and sieved through a sieve in sequence to obtain the alkali residue.

6. The solid waste-based polymer according to claim 5, characterized in that: The initial water content of the alkali residue stock solution is not less than 90%.

7. The solid waste-based polymer according to claim 1 or 2, characterized in that: Measured in weight percentage, the CaO content in the alkali slag is greater than 40%.

8. A method for preparing a solid waste-based polymer, characterized in that: The steps include: Step S1, mixing coal gasification slag, slag, alkaline slag, phosphogypsum and sand to obtain a mixture; Step S2, adding water to the mixture and stirring to obtain the solid waste-based polymer; Wherein, the weight ratio of the coal gasification slag, the slag, the alkaline slag and the phosphogypsum is (30-45): (30~45):(5~20):(5~20); the weight ratio of the sand to the sum of the weight of the coal gasification slag, the slag, the alkali slag and the phosphogypsum is (3~5):1; the weight ratio of the added water to the solid waste-based polymer is (0.12~0.15):

1.

9. Use of the solid waste-based polymer according to any one of claims 1 to 7 or the solid waste-based polymer prepared by the preparation method according to claim 8 in road construction.

10. A roadbed material, characterized in that: A hardened product comprising a solid waste-based polymer according to any one of claims 1 to 7 or a solid waste-based polymer prepared by the preparation method according to claim 8; Preferably, the solid waste-based polymer is loaded into a mold coated with a release agent and the mold is placed on a vibration table, the solid waste-based polymer is vibrated to form, the molded solid waste-based polymer is demolded after curing for 20 to 30 hours, and after demolding, it is cured for 7 to 28 days at a temperature of 18° C. to 22° C. and a relative humidity of 93% to 97% to obtain the hardened product.